Dysleksja, czyli specyficzne trudności w nauce czytania i pisania w świetle aktualnej literatury przedmiotu - Augustyniak, Ewelina (Acta Universitatis Lodziensis. Folia Librorum, 2010)
This article discusses the problem of the specific difficulties in learning to read and write in light of current literature. Dyslexia, because of her speech, occupies an important place among the publications appearing on the Polish and international book market. The article is a review of publications in terms of chronological and thematic. Also shows the important role of the teacher-librarian in the process of re-education student with dyslexia and the need to create a special work program in the school library, supportive therapy children with specific difficulties in mastering the basic principles of reading and writing.